2023
DOI: 10.21203/rs.3.rs-2735199/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Role of Vitamin D On Interferon- Levels in Indonesian Children with Down Syndrome And Its Contributing Factors: A Cross-sectional Study

Abstract: Background Vitamin D (VD) plays a role in reducing the risk of diseases related to the immune system, including autoimmune diseases, by inhibiting proinflammatory cytokines such as IFN-γ. Children with Down syndrome (DS) are known to have interferonopathy due to trisomy 21 and have lower VD levels. This study aimed to evaluate the VD profile in Indonesian children with DS and its correlation with IFN-γ.Methods This study was conducted from March 2020 to June 2021 at Dr. Soetomo General Hospital, Surabaya. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
1
0
0
Order By: Relevance
“…In the context of children with Down syndrome in Indonesia, the consumption of meat and milk, as well as exposure to sunlight are significant factors that influence vitamin D (VD) levels. Our study aligns with previous research that has demonstrated a correlation between consistent milk consumption and a decreased likelihood of autoimmune illness in children diagnosed with Down syndrome [32].…”
Section: Resultssupporting
confidence: 92%
“…In the context of children with Down syndrome in Indonesia, the consumption of meat and milk, as well as exposure to sunlight are significant factors that influence vitamin D (VD) levels. Our study aligns with previous research that has demonstrated a correlation between consistent milk consumption and a decreased likelihood of autoimmune illness in children diagnosed with Down syndrome [32].…”
Section: Resultssupporting
confidence: 92%